Biophysical Screening Pipeline for Cryo-EM Grid Preparation of Membrane Proteins - Niebling, Stephan; Veith, Katharina; Vollmer, Benjamin; Lizarrondo, Javier; Burastero, Osvaldo; Schiller, Janina; Struve García, Angelica; Lewe, Philipp; Seuring, Carolin; Witt, Susanne; García-Alai, María (Frontiers in Molecular Biosciences, 2022)
Successful sample preparation is the foundation to any structural biology technique. Membrane proteins are of particular interest as these are important targets for drug design, but also notoriously difficult to work with. For electron cryo-microscopy (cryo-EM), the biophysical characterisation of sample purity, homogeneity and integrity, as well as biochemical activity are the prerequisite for the preparation of good quality cryo-EM grids as these factors impact the result of the computational reconstruction. Here, we present a quality control pipeline prior to single particle cryo-EM grid preparation using a combination of biophysical techniques to address the integrity, purity and oligomeric states of membrane proteins and its complexes to enable reproducible conditions for sample vitrification. Differential scanning fluorimetry following the intrinsic protein fluorescence (nDSF) is used for optimising buffer and detergent conditions whereas mass photometry and dynamic light scattering are used to assess aggregation behaviour, reconstitution efficiency and oligomerization. The data collected on nDSF and mass photometry instruments can be analysed with web servers publicly available at spc.embl-hamburg.de. Case studies to optimise conditions prior to cryo-EM sample preparation of membrane proteins present an example quality assessment to corroborate the usefulness of our pipeline.